Mutations in the A subunit affect yield, stability, and protease sensitivity of nontoxic derivatives of heat-labile enterotoxin. - Magagnoli, C (1996)
Heat-labile toxin (LT) is a protein related to cholera toxin, produced by enterotoxigenic Escherichia coli strains, that is organized as an AB5 complex. A number of nontoxic derivatives of LT, useful for new or improved vaccines against diarrheal diseases or as mucosal adjuvants, have been constructed by site-directed mutagenesis. Here we have studied the biochemical properties of the nontoxic mutants LT-K7 (Arg-7-->Lys), LT-D53 (Val-53-->Asp), LT-K63 (Ser-63-->Lys), LT-K97 (Val-97-->Lys), LT-K104 (Tyr-104-->Lys), LT-K114 (Ser-114-->Lys), and LT-K7/K97 (Arg-7-->Lys and Val-97-->Lys). We have found that mutations in the A subunit may have profound effects on the ability to form the AB5 structure and on the stability and trypsin sensitivity of the purified proteins. Unstable mutants, during long-term storage at 4 degrees C, showed a decrease in the amount of the assembled protein in solution and a parallel appearance of soluble monomeric B subunit. This finding suggests that the stability of the B pentamer is influenced by the A subunit which is associated with it. Among the seven nontoxic mutants tested, LT-K63 was found to be efficient in AB5 production, extremely stable during storage, resistant to proteolytic attack, and very immunogenic. In conclusion, LT-K63 is a good candidate for the development of antidiarrheal vaccines and mucosal adjuvants.